ANALISIS STRATEGI GURU DALAM MENANAMKAN NILAI PENDIDIKAN KARAKTER KEDISIPLINAN DI SEKOLAH DASAR - Mina Listiana; Encep Andriana; Siti Rokmanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT The character of discipline is very important to instill in students. In SDN Cipocok Jaya 2, the value of discipline has been instilled. Such as carrying out student picket duty, greeting students, and attending the flag ceremony. This is shown by the teacher's efforts in sanctioning violations of school rules committed by students. However, there are still some students who violate the rules, including students who often come to school late, do not wear uniform attributes, or are not fully dressed during the ceremony. Therefore, it is important for a teacher to know what strategies are used to instill the value of character education in students. This study aims to determine how the teacher's strategy in instilling the value of discipline character education in class VI SDN Cipocok jaya 2. This research approach is a qualitative approach with descriptive qualitative research type. This research data collection procedure carried out at Cipocok jaya 2 SDN by collecting data using interview, observation and documentation techniques. This research procedure is divided into 4 stages, namely: planning stage, preparation stage, implementation stage and reporting stage. The results showed that the teacher's strategy in instilling the value of disciplinary character education in grade VI students at Cipocok Jaya 2 Elementary School is to make school regulations, compile lesson plans and devices, habituation and giving rewards and educative punishments.